2019
DOI: 10.31234/osf.io/k7g4a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Early Childhood Inhibitory Touchscreen Task

Abstract: Research into the earliest development of inhibitory control (IC) is limited by a lack of suitable tasks. In particular, commonly used IC tasks frequently have too high language and working memory demands for children under 3 years of age. Furthermore, researchers currently tend to shift to a new set of IC tasks between toddlerhood and early childhood, raising doubts about whether the same function is being measured. Tasks that are structurally equivalent across age could potentially help resolve this issue. I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 48 publications
3
36
0
Order By: Relevance
“…The authors also found low correlations among the executive function tasks in their study and mention that limited task variation in the Go/No-Go task was a problem (for more information please see Willoughby et al, 2019). Similarly, Petersen et al (2016) and Holmboe et al (2019) mention variability issues with regards to inhibition tasks. Petersen et al (2016) explain that ceiling and floor effects are associated with lower variability in the measured construct, which increases Type II error and reduces power to detect associations with other variables.…”
Section: Limitationsmentioning
confidence: 84%
See 4 more Smart Citations
“…The authors also found low correlations among the executive function tasks in their study and mention that limited task variation in the Go/No-Go task was a problem (for more information please see Willoughby et al, 2019). Similarly, Petersen et al (2016) and Holmboe et al (2019) mention variability issues with regards to inhibition tasks. Petersen et al (2016) explain that ceiling and floor effects are associated with lower variability in the measured construct, which increases Type II error and reduces power to detect associations with other variables.…”
Section: Limitationsmentioning
confidence: 84%
“…An issue in the present study was ceiling effects within our EF performance data. Ceiling effects are a consistent issue within the literature where scholars aim to measure EFs in children, especially when measuring inhibition (Holmboe et al, 2019;Willoughby et al, 2019). For example, Willoughby et al (2019) found floor and ceiling effects on several inhibition tasks with children (Go/No-Go, Silly Sound Stroop tasks, and Spatial Conflict Arrows).…”
Section: Limitationsmentioning
confidence: 97%
See 3 more Smart Citations